Postoperative nausea and vomiting following orthognathic surgery - Phillips, C.; Brookes, C.D.; Rich, J.; Arbon, J.; Turvey, T.A. (International journal of oral and maxillofacial surgery, 2015)
The purpose of this study was to assess the incidence and risk factors associated with postoperative nausea (PON) and vomiting (POV) after orthognathic surgery. A review of the clinical records of consecutively enrolled subjects (2008–2012) at a single academic institution was conducted between 9/2013 and 3/2014. Data on the occurrence of PON and POV and potential patient-related, intraoperative, and postoperative explanatory factors were extracted from the medical records. Logistic models were used for the presence/absence of postoperative nausea and vomiting separately. Data from 204 subjects were analyzed: 63% were female, 72% Caucasian, and the median age was 19 years. Thirty-three percent had a mandibular osteotomy alone, 27% a maxillary osteotomy alone, and 40% had bimaxillary osteotomies. Sixty-seven percent experienced PON and 27% experienced POV. The most important risk factors for PON in this series were female gender, increased intravenous fluids, and the use of nitrous oxide, and for POV were race, additional procedures, and morphine administration. The incidence of PON and POV following orthognathic surgery in the current cohort of patients, after the introduction of the updated 2007 consensus guidelines for the management of postoperative nausea and vomiting, has not decreased substantially from that reported in 2003–2004.